Memasak Wader Liwet: Sebuah Upaya Melestarikan Warisan Budaya Takbenda - Bimo Haryo Yudhanto (Universitas Muhammadiyah Makassar, 2025)
This article aims to identify the preservation of the intangible cultural heritage of wader liwet by the Klayar community in Gunungkidul Regency. In 2023, wader liwet was designated as one of Indonesia's Intangible Cultural Heritage based on a proposal from the Special Region of Yogyakarta Province. Wader liwet is a traditional fish-based dish originating from the Klayar hamlet (dusun). To this day, the Klayar community continues to preserve wader liwet by consistently preparing and serving it during significant events. For the Klayar community, wader liwet embodies their identity through culinary knowledge. It also serves as a medium connecting the community with their ancestors. This article aims to uncover the structure of knowledge within the community regarding wader liwet by identifying the narratives embedded in each stage of its preparation. The research methods employed include observation and interviews to identify key elements in this cultural practice. The results of this research are expected to provide insights into the importance of wader liwet as part of the cultural identity of the Klayar community, as well as offer a preservation model that can be adapted by other communities. This article not only focuses on the food aspect but also on strengthening identity and the sustainability of intangible cultural heritage in Indonesia.